PARAGARD AND MIRENA AS MODERN INTRAUTERINE DEVICES - Amirta Sukantan, Theiva; Toya, I N; Adioka, I G M (Bali Journal of Medical and Health Sciences; vol 1no1 2013, 2013)
Normal 0 false false false EN-US X-NONE X-NONE MicrosoftInternetExplorer4 Th e re a re two kinds of mode r n I U D s: Copp e r - b e aring a nd prog e st in - r e leasin g . I UD stands for I ntr a Ut e rine D e vic e , a T - sha p e d pi e c e of plastic that is pla ce d ins i de the u t e rus. T h e most c om m on c opp e r - b ea ri n g I UD is the Par a gard[ R ] C opp e r T 38 0 A . The on l y p r o g e st in - r e le a si n g I U D now a v a i l a ble is M irena[R ] . The c opp e r I U D, ParaGard , wo r ks for a s lo n g a s 12 y ea rs. Copp e r b a s e d in t r a ute r ine d e vi c e s a r e t o x ic to spe r ms a nd a r e a lso known a s no n - hormon a l in t r a ute r i n e d e vic e s. The hormon a l I U D, M irena , must be r e p l ace d a ft e r 5 y e a rs. This d e vice fu n c t i ons b y r e l e a sing le v onor g e st r e l , a p r og e st i n that h e lps in c on t r a ce pt i on. This t y pe o f I U Ds p re v e nts the f e rti l i z a t i on of the e gg b y c a using spe r ms to b ec ome ine f f e c t i ve a nd a lso mak e s the mucus in the c e rvix s t ic k y a nd a l m ost i m p e rm ea ble. B oth t y p e s make it more d i f f icult f or spe r m t o f e rtil iz e the e g g . /* Style Definitions */ table.MsoNormalTable {mso-style-name:"Table Normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-priority:99; mso-style-qformat:yes; mso-style-parent:""; mso-padding-alt:0in 5.4pt 0in 5.4pt; mso-para-margin:0in; mso-para-margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:11.0pt; font-family:"Calibri","sans-serif"; mso-ascii-font-family:Calibri; mso-ascii-theme-font:minor-latin; mso-fareast-font-family:"Times New Roman"; mso-fareast-theme-font:minor-fareast; mso-hansi-font-family:Calibri; mso-hansi-theme-font:minor-latin; mso-bidi-font-family:"Times New Roman"; mso-bidi-theme-font:minor-bidi;}